Playing with fire (financial independence retire early) : how far would you go for financial freedom? - Rieckens, Scott, 1983- (New World Library, 2019)
"A detailed profile of an alternative lifestyle known as FIRE (Financial Independence Retire Early), in which participants strive to retire in their 30s or 40s by living frugally, saving creatively, and investing efficiently. Participants in the movement share personal stories and financial strategies with the author"--